Trend of Ultraprocessed Product Intake Is Associated with the Double Burden of Malnutrition in Mexican Children and Adolescents (2022)
ABSTRACT: Background: Ultraprocessed products (UPPs) have been associated with unfavorable health outcomes; however, until now, they have not been associated with the coexistence of undernutrition and overnutrition, known as the double burden of malnutrition (DBM) at the individual level. Methods: Cross-sectional analyses were performed on data collected from children and adolescents participating in the 2006 and 2016 Mexican National Health and Nutrition Surveys. The food and beverages reported in the food frequency questionnaire (SFFQ) were classified as UPPs as defined by the NOVA classification system. Associations of UPPs with anemia, excess weight, and the DBM were estimated with logistic regression models. A pseudo-panel was generated using the cohorts of children born from 1997 to 2001 to estimate the effect of the UPPs on anemia, excess weight, and the DBM. Results: The consumption of UPPs (% energy) was higher in 2016 (children 30.1% and adolescents 28.3%) than in 2006 (children 27.3% and adolescents 23.0%) in both age-groups. The higher contribution of UPPs was positively associated with excess weight and the DBM in children’s lower tertile of socioeconomic status (SES) and the DBM in higher tertile of SES in adolescents. The pseudo-panel analysis shows the positive association between UPPs and DBM in lower SES. Conclusions: These results provide evidence of the association between the consumption of UPPs and the DBM and excess weight in children and adolescents.